Chapter 14: Medication Safety (Foundations in Clinical Pharmacy Practice, 2025)
AuthorDr. Anurag Sahu, Clinical Pharmacist, Department of Clinical Pharmacology, Apollo SAGE Hospital, Bhopal, Madhya Pradesh, IndiaAbstractMedication safety systems provide comprehensive frameworks for preventing, identifying, and mitigating medication-related harm through integrated approaches addressing system vulnerabilities throughout the medication use process. Error prevention strategies employ human factors engineering, high-alert medication safeguards, technology utilization, and standardized communication techniques creating multiple layers of protection against medication misadventures. Risk management methodologies implement proactive assessment through failure mode analysis, medication use evaluation, root cause investigation, and simulation training identifying system weaknesses before patient harm occurs. Quality assurance programs develop performance indicators, compliance monitoring systems, peer review processes, and continuous improvement methodologies ensuring consistent adherence to safe medication practices across diverse healthcare settings. Reporting systems establish voluntary and mandatory event notification mechanisms, just culture implementation, aggregate data analysis, and systematic learning dissemination transforming individual incidents into system-wide improvement opportunities. Safety initiatives target high-risk medications including anticoagulants, insulin, opioids, and chemotherapy through specialized protocols, technology implementation, and process redesign addressing known vulnerability points. This comprehensive approach shifts focus from individual blame to system improvement through standardization, simplification, automation, and education creating resilient medication systems capable of preventing errors despite human fallibility and complex healthcare environments.Keywords: Medication Error Prevention, System Reliability, Safety Culture, Risk Mitigation, Adverse Event ReductionVIEW PDF